Objects with symbolic meaning: 16 directions to inspire design for well-being. (8th May 2019) - Casais, Mafalda; Mugge, Ruth; Desmet, Pieter
The symbolic meaning of a product can contribute to people's well-being. Previous research (Casais et al., 2016) has identified six distinct well-being enhancing symbolic meanings in products (based on Ryff, 1989): positive relations with others, personal growth, autonomy, environmental mastery, purpose in life, and self-acceptance. To support design activities with a focus on symbolic meaning, the current paper introduces 16 design directions that can be used for ideation and conceptualisation. These directions were developed in a two-stage process. First, 50 product examples were selected for their ability to encourage one or more of the six symbolic meanings. Second, these examples were used as stimuli in individual sessions with seven designers and design researchers. Participants analysed the product examples to infer the underlying design intentions, which were used to formulate the 16 symbolic meaning-focused 'design for subjective well-being' strategies.